Screening performances of abnormal first‐trimester ductus venosus blood flow and increased nuchal translucency thickness in detection of major heart defects. (12th October 2015) - Karadzov‐Orlic, Natasa; Egic, Amira; Filimonovic, Dejan; Damnjanovic‐Pazin, Barbara; Milovanovic, Zagorka; Lukic, Relja; Mandic, Vesna; Joksic, Ivana; Vukomanovic, Vladimir; Kosutic, Jovan; Djuricic, Slavisa; Mikovic, Zeljko
Abstract: Objective: The aim of this study was to evaluate the screening performances of abnormal ductus venosus (DV) blood flow for the detection of heart defects in chromosomally normal fetuses with increased nuchal translucency (NT) thickness at 11–13 + 6 weeks' gestational in a population of singleton pregnancies. Methods: During an 8‐year period, all singleton pregnancies from 11 + 0 to 13 + 6 weeks were scanned for NT and DV blood flow assessment. Two groups of cases with abnormal NT were evaluated: NT ≥ 95th and NT ≥ 99th centile. DV waveforms were considered to be abnormal if the a‐wave was reversed or absent (R/A). Results: Addition of DV R/A a‐wave to either NT ≥ 95th or NT ≥ 99th percentile increased specificity ( p < 0.001 and p < 0.001, respectively), but not screening performances in detection of major heart defects ( p = 0.73 and p = 0.91, respectively). Combination of DV R/A a‐wave with NT ≥ 95th or NT ≥ 99th centile correlated with right heart defects ( p = 0.024 and p = 0.013, respectively). Conclusions: In chromosomally normal fetuses, addition of abnormal DV a‐wave to increased NT does not improve screening performances of NT in detection of major hearts defects in first trimester. However, there is correlation of such parameter with right heart defects and AV septal defects. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Measurement of NT thickness in first trimester is a standard clinical practice of prenatal screening for heart defects. There are conflicting results whether the addition of qualitative assessment of ductus venosus flow improves screening performances of increased NT for heart defects. What does this study add? Addition of reduced or absent DV a‐wave to increased NT improves its specificity for detection of major heart defects during the first trimester. Reduced or absent a‐wave of DV flow in combination with increased NT correlates with increased risk of right heart defects and AV septal defects.